Children’s Mental Health Protection Policy Amid the Covid-19 Pandemic - Eka Yektiningsih; Natangsa Surbakti; Nuria Siswi Enggarani; Moh Indra Bangsawan; Dewi Kusuma Diarti; Arief Budiono (Humanistic Network for Science and Technology (HNST), 2021)
Article 28 B of the 1945 Constitution of the Republic of Indonesia affirms that children have the right to be protected from discrimination, economic and sexual exploitation, neglect, cruelty, violence, persecution, injustice and other mistreatment. This study aims to 1) Describe child protection policies in the midst of the COVID-19 pandemic, 2) Describe the children's health protection policy during the covid-19 pandemic. This was a normative legal research conducted by examining library materials or secondary data. It used the statutory approach, with a descriptive method. The policy of protecting children in the midst of the Covid-19 pandemic is based on Law Number 35 of 2014 concerning Child Protection which includes not only protection of the child's body and soul, but also spiritually, physically and socially. However, at the level of implementation, the government is more focused on protecting children from Covid-19 cases and has not been optimal in helping children face the burden of mental health during the Covid-19 pandemic. Therefore, the government needs to deal with mental health issues for children and adolescents during the pandemic by making regulations that focus on the direction of each policy towards the realization of a society that cares about mental health.Keywords: policy; child mental health; covid-19